Endovascular stenting of tracheoinnominate fistula after tracheostomy in a 14-year-old boy - Mi-Hye Bae; Yun-Jin Lee; Sang Ook Nam; Hye-Young Kim; Chang Won Kim; Young Mi Kim (Korean Pediatric Society, 2016)
Tracheoinnominate artery fistula is a rare, fatal complication of tracheostomy, and prompt diagnosis and management are imperative. We report the case of tracheoinnominate artery fistula after tracheostomy in a 14-year-old boy with a history of severe periventricular leukomalacia, hydrocephalus, cerebral palsy, and epilepsy. The tracheoinnominate artery fistula was successfully treated with a stent graft insertion via the right common femoral artery. Endovascular repair of the tracheoinnominate artery fistula via stent grafting is a safe, effective, and minimally invasive treatment for patients in poor clinical conditions and is an alternative to traditional open surgical treatment.